English vocabulary in use : advanced - McCarthy, Michael (Cambridge University Press, 2002)
The fourth in the family of best-selling vocabulary reference and practice books from elementary to advanced level. Vocabulary is clearly presented and contextualized on left-hand pages with practice activities on facing right-hand pages. The perfect choice for advanced-level students wanting to build their vocabulary skills. English Vocabulary in Use: Advanced includes over 2,000 new words and expressions which are presented and practised in typical contexts appropriate to this level.